Voices from the Warsaw Ghetto writing our history - Roskies, David G. 1948-; Kassow, Samuel D. 1946- (Yale University Press, 2019)
Hidden in metal containers and buried underground during World War II, these writings from the Warsaw Ghetto record the Holocaust in the words of its first interpreters, the victims themselves. Gathered clandestinely by an underground ghetto collective called Oyneg Shabes, this anthology comprises reportage, diaries, prose, poems, jokes, and sermons that capture the heroism, tragedy, humor, and social dynamics of the ghetto. Miraculously surviving the devastation of war, this extraordinary archive encompasses a vast range of voices-young and old, men and women, the pious and the secular, optimists and pessimists-and chronicles different perspectives on the topics of the day while also preserving rapidly endangered cultural traditions. Described by David G. Roskies as "a civilization responding to its own destruction," these texts tell the story of the Warsaw Jews in real time, against time, and for all time
"A companion volume to the Posen Library of Jewish Culture and Civilization"
Keywords: Podziemne Archiwum Getta Warszawskiego; Geschichte 1939-1943; Getto; Judenverfolgung; Warschau; World War, 1939-1945 / Jews / Poland / Warsaw; Jews / Poland / Warsaw / History / 20th century; World War, 1939-1945 / Personal narratives, Jewish; Holocaust, Jewish (1939-1945) / Poland / Warsaw / Personal narratives; Warsaw (Poland) / History / 20th century; Erlebnisbericht; Quelle; Anthologie